PVP/ZIF-8-Derived Zn, Ni Co-loaded N-Doped Porous Carbon as a Catalyst for an Efficient Hydrogen Evolution Reaction - Jing, Yanqiu; Lei, Qiang; Hu, Gang; He, Jixian; Lei, Xiao; Wang, Fei; Li, Junju; Yang, Yide; Zhang, Xuewei (Frontiers in Chemistry, 2020)
Exploring catalysts with low cost and excellent performance for hydrogen evolution reaction (HER) is still a significant challenge. In this work, zeolitic imidazolate framework-8 (ZIF-8), hybridizing with polyvinylpyrrolidone, was used to prepare Zn, Ni co-loaded N doped porous carbon (ZnNi/NPC) via a facile absorption and pyrolysis process. The as-prepared ZnNi/NPC was used as catalyst for hydrogen evolution reaction (HER). This experiments show that the porous structure and Ni doping have great influence on the HER activity of the catalyst. Comparing with Zn/NC and Zn/NPC, ZnNi/NPC exhibits a superior HER activity with the overpotential of 198 mV and the Tafel slope of 69.2 mV dec-1. ZnNi/NPC also shows excellent physical and chemical stability during the HER process. Considering the lower cost and excellent HER performance of ZnNi/NPC, this work provides an attractive solution to fabricate non-precious materials and offers a possible new strategy to replace Pt-based electrocatalysts for HER.